Pharmacokinetics of fixed-dose combination of rosuvastatin 20 mg and ezetimibe 10 mg compared to concurrent administration of individual tablets in healthy Korean subjects - Hwang, Inyoung (Transl Clin Pharmacol, 2018)
This study aimed to compare the pharmacokinetics of fixed-dose combination (FDC) tablet of rosuvastatin 20 mg/ezetimibe 10 mg with that of concurrent administration of individual rosuvastatin 20 mg tablet and ezetimibe 10 mg tablet in healthy subjects. A randomized, open label, single-dose, two-way crossover study was conducted. Subjects randomly received test formulation (FDC tablet of rosuvastatin 20 mg/ezetimibe 10 mg) or reference formulation (co-administration of rosuvastatin 20 mg tablet and ezetimibe 10 mg tablet). After 2 weeks of washout, subjects received the other treatment. Blood samples were collected up to 72 hours post-dose in each period. Plasma concentrations of rosuvastatin, ezetimibe and total ezetimibe (ezetimibe + ezetimibe glucuronide) were analyzed by liquid chromatography-tandem mass spectrometry (LC/MS/MS). The geometric mean ratio (GMR) of C(max) and AUC(last) (90% confidence interval, CI) for rosuvastatin was 1.036 (0.979–1.096) and 1.024 (0.981–1.070), respectively. The corresponding values for ezetimibe were 0.963 (0.888–1.043) and 1.021 (0.969–1.074), respectively. The corresponding values for total ezetimibe were 0.886 (0.835–0.940) and 0.983 (0.946–1.022), respectively. FDC tablet containing rosuvastatin 20 mg and ezetimibe 10 mg is bioequivalent to the co-administration of commercially available individual tablets of rosuvastatin and ezetimibe as GMR with 90% CI of C(max) and AUC(last) of rosuvastatin, ezetimibe and total ezetimibe were contained within conventionally accepted bioequivalence criteria.